The Effect of Non Performing Loan and Capital Adequacy Ratio on Return on Assets in Bank Victoria International, Tbk Period 2009-2018 - Waluyo Jati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of Non-Performing Loans and Capital Adequacy Ratio on Return on Assets at PT. Bank Victoria International, Tbk. 2009-2018 period The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study that Non Performing Loans have a significant effect on Return on Assets by 60.4%, hypothesis testing is obtained t count> t table or (3.496> 2.306). Capital Adequacy Ratio has a significant effect on Return on Assets of 2.8%, hypothesis testing obtained t count <t table or (-0.477 <2.306). Non-Performing Loan and Capital Adequacy Ratio simultaneously have a significant effect on Return on Assets, the regression equation is Y = 8.666 + 0.569X1 + 0.049X2 and a determination value of 60.8%, hypothesis testing is obtained by the value of F count> F table or (5,431> 4,350).